Starvation and the state famine, slavery, and power in Sudan, 1883-1956 - Serels, Steven 1982- (Palgrave series in Indian Ocean world studies, 2013)
For much of its recent history, Sudan has been beset by devastating famines that have killed countless people and powerfully reshaped its society. However, as this historical study of food insecurity in the region shows, there was no necessary correlation between natural disasters, decreased crop yields, and famine in Sudan. Rather, repeated food crises since the late nineteenth century were the result of inter-generational, exploitative processes that transferred the resources of victim communities to the state and to a small group of non-state elites. This dynamic fundamentally transformed the social, political, and economic structures underpinning Sudanese society and prevented many communities from securing necessary subsistence. On one hand, food crises facilitated the British-led conquest of Sudan and subsequently allowed British imperial agents, acting through the Anglo-Egyptian government, to seize control of many of Sudan's natural resources. At the same time, however, a number of indigenous elites were also able to position themselves so as to further augment their prestige and economic wealth. At independence, these elites were handed control of the state and, in the years that followed, they continued many of the policies that had impoverished their countrymen